Arm/shoulder specific strength device for throwers - Agrebi, B.; Bouagina, R.; Fray, A.; Abidi, H.; Guemira, F.; Bezzarga, M.; Guelmami, N.; Houas, N.; Kasmi, S.; Ben Mohamed, O.; Khalifa, R. (American Journal of Sports Science, 2020)
Research has proposed various ways to develop ballistic/explosive arm rotational movements for throwers but demonstrated inherent limitations for the lack of traditional resistance training respecting sport-specific tasks. A prototype device was conceived for ballistic multi-joint throwing exercises. Forty-three high-level competitive U19 male handball players participated in the study aged 18.42 ± 1.17 years; 82.36 ± 3.07 mass kg; and 184.91 ± 6.06 m height. Subjects underwent tests on the ASSSD, which operates into consecutive accelerative and decelerative actions, for throwing characteristics determination. Concentric (CON) and eccentric (ECC) variables during overhead throws as force, power, velocity, acceleration and angle when occurred peak force (PF), power (PP) and velocity (PV) were defined. The relative reliability was calculated using the intraclass correlation coefficients (ICCs) showing strong agreement between trials. The absolute reliability was analyzed using standard error of measurement SEM (0.03-2.75), and Coefficients of variation CVs (2.84-4.59%) for studied variables, reveals excellent interday reliability. Validity was assessed using linear regressions, r and p values showing good relationship between PF and PP gathered from ASSSD and isokinetic peak torques at different angular velocities of dominant arm (DA). The device sensitivity was verified when assessing CON-ECC PF, CON-ECC PP and CON PV with elite/non-elite players. The ASSSD has demonstrated its reliability, validity and sensitivity intended for testing, training monitoring and sport performance assessment.